Behavioral endocrinology (Cambridge, Mass. : MIT Press, 2002)
This behavioral endocrinology text provides detailed information on what hormones are, how they affect cells, and how such effects can alter the behavior of animals, including humans. Presenting a broad continuum of levels of analysis, from molecular to evolutionary, the book discusses how genes work, the structure of cells, the interactions of endocrine organs, the behavior of individuals, the structure of social hierarchies, and the evolution of mating systems.
Environmental factors influencing hormone secretion / Rae Silver and Lance J. Kriegsfeld
Keywords: bihevioralna ekologija